Effects of wing inboard plan-form modifications on lift, drag, and longitudinal stability at Mach numbers from 1.0 to 2.3 of a rocket-propelled free-flight model with a 52.5 degree sweptback wing of aspect ratio 3 - Henning, Allen B.; United States. National Advisory Committee for Aeronautics (Washington, D.C. : National Advisory Committee for Aeronautics, 1957)
An investigation was made to determine the effects of wing inboard plan-form modifications on the lift, drag, and longitudinal characteristics of a rocket-propelled free-flight model. The model had a body of fineness ration 17.4, a modified wing with a basic plan form swept back 52.5 degrees and an aspect ratio of 3, and inline horizontal tail surfaces which were aerodynamically pulsed continuously throughout the flight.
NACA Research Memorandum L57D29.
"June 19, 1957."
Title from cover.
Includes bibliographical references.
Mode of access: Internet.
Keywords: Charts, diagrams, etc; Mach number; Stability; Drag (Aerodynamics); Lift (Aerodynamics); Aerofoils -- Testing